2016
DOI: 10.2217/whe.15.91
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Iron Deficiency and Anemia in Pregnant Women: An Observational French Study

Abstract: Aim:We explored the prevalence and management of iron deficiency and anemia among pregnant women in France. Patients & methods: In this prospective, observational, multicenter registry study, randomly selected investigators (gynecologists/obstetricians/midwives registered in the CEGEDIM ® database) assessed pregnant women presenting for a consultation. Participants completed a questionnaire at study inclusion. Results: A total of 1506 patients were enrolled by 95 investigators. Overall, investigators estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
3
16
0
2
Order By: Relevance
“…The burden of anaemia in our study was similar to other studies in Ethiopia [40, 41], and it was most likely caused by iron deficiency [42]. However, our findings show that that the uptake of Iron-folic-acid tablet supplementation and health service utilisation for anaemia was low.…”
Section: Discussionsupporting
confidence: 85%
“…The burden of anaemia in our study was similar to other studies in Ethiopia [40, 41], and it was most likely caused by iron deficiency [42]. However, our findings show that that the uptake of Iron-folic-acid tablet supplementation and health service utilisation for anaemia was low.…”
Section: Discussionsupporting
confidence: 85%
“…It should be emphasized that other types of anemia were found in 11.8% of pregnant women in this longitudinal investigation [7]. Data from a cohort study of 1,478 pregnant women showed that 15.8% of French women had maternal anemia in 2013 and 2014 [10]. Of these women, approximately 31% had iron deficiency [10].…”
Section: Prevalence Of Maternal and Iron Deficiency Anemiamentioning
confidence: 55%
“…Data from a cohort study of 1,478 pregnant women showed that 15.8% of French women had maternal anemia in 2013 and 2014 [10]. Of these women, approximately 31% had iron deficiency [10]. Asia has the second-highest rate of maternal anemia in the world [1].…”
Section: Prevalence Of Maternal and Iron Deficiency Anemiamentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of ID and IDA is higher in pregnancy, and IDA affects 18-38% of pregnant women worldwide (Lopez et al 2016; World Health Organization 2015). The worldwide prevalence of ID is twice that of IDA (Camaschella 2015), and studies in Western nations report ID in as many as 60% of pregnant women (Arija et al 2013; da Costa et al 2016; Harvey et al 2016; Ribot et al 2012). …”
Section: Perinatal Iron Deficiencymentioning
confidence: 99%